Do paediatricians miss the diagnosis of obesity?. (29th September 2015) - Abbey, I; Rudolf, M
Abstract : Aims: To evaluate how often paediatricians recognise and manage obesity in children they see in outpatient clinics. Methods: An audit of outpatient clinic consultations during a calendar month in both general paediatrics and paediatric endocrinology. All children with a body mass index (BMI) ≤ 98th percentile had their notes reviewed for evidence that the clinician had recognised their obesity, arranged appropriate investigations for hormonal causes and co morbidities and given lifestyle advice or referral to a community obesity programme. The results were fed back during a post clinic meeting. Clinicians were given written material on the National Institute for Health and Clinical Excellence (NICE) obesity guidelines and the local community obesity programme. UK BMI management charts were displayed in all clinic rooms. A repeat audit evaluated any change in obesity recognition and management. Results: A total of 157 patient visits occurred during the audit period, including 21 obese children. 6/10 and 5/11 of the obese children attending the paediatric endocrinology and general clinics, respectively, were recognised as having a weight problem. Fewer than half the children were asked for appropriate family history, had a body mass index (BMI) measurement, or investigations for hormonal causes or co morbidities; apart from in the endocrinology clinic where 8/10 obese children had thyroid function tested. 3/10 in the endocrinology clinic and 3/11 in the general clinic had lifestyle advice or referrals to the obesity service. In the repeat audit 15/147 patients attending either the endocrinology or general clinics were obese. 5/9 and 2/6 in the endocrine and general clinics, respectively, were recognised as obese; no statistical change from the initial audit. There was no increase in the numbers of diagnosed obese children being investigated or offered help with weight loss. Conclusion: A large proportion of the obese children attending endocrinology and general clinics in a teaching hospital are not recognised as having a weight problem and less than half are investigated or managed in accordance with NICE guidance. Feedback of the audit results, displaying BMI charts in clinic rooms, and providing written information on the NICE guidelines and referral options, did not improve the results.